2006
DOI: 10.1002/humu.9401
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectra ofABCC8 gene in Spanish patients with hyperinsulinism of infancy (HI)

Abstract: Hyperinsulinism of Infancy (HI) is a clinical disorder characterized by deregulation of insulin secretion that leads to profound hypoglycemia. Mutations in genes encodingthe ATP-regulated potassium channels of the pancreatic β-cell, namely ABCC8 (SUR1) and KCNJ11 (Kir6.2), are the major genetic known cause of the disease. To elucidate the genetic etiology of HI in the uncharacterized Spanish population, we conducted extensive sequencing analysis of the ABCC8 (83.5Kb) and KCNJ11 (1.7Kb) genes in 34 Spanish HI p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 47 publications
5
39
2
3
Order By: Relevance
“…In our study, a genetic diagnosis was obtained in 56% of patients with CHI tested, similar to figures reported in other studies (4,16,17,18), although slightly lower than that found in the only previous study in a Spanish population (19). ABCC8 inactivating mutations are the leading genetic cause of CHI in our patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, a genetic diagnosis was obtained in 56% of patients with CHI tested, similar to figures reported in other studies (4,16,17,18), although slightly lower than that found in the only previous study in a Spanish population (19). ABCC8 inactivating mutations are the leading genetic cause of CHI in our patients.…”
Section: Discussionsupporting
confidence: 89%
“…An exception within this group is the patient with compound heterozygous mutation in ABCC8 (patient 5) who did respond to diazoxide treatment. This patient had a p.Ala578_Leu582dup mutation in the paternal allele, a mutation that has been described to be associated with different situations in two patients with the mutation in heterozygosis and paternally inherited, who had a severe phenotype and did not respond to diazoxide treatment (5,20), and in one patient with a compound heterozygous mutation, who was managed with continuous feeding (19). In the maternal allele, our patient has a novel missense mutation p.Ala1575Pro, and in silico analysis showed discrepant results (Table 3).…”
Section: Discussionmentioning
confidence: 94%
“…Diffuse CHI has been described in the literature with paternally inherited ABCC8/KCNJ11 mutations. Fernandez-Marmiesse et al (10) reported five patients with paternally inherited K ATP mutations and whose post pancreatectomy pathology result was not consistent with that of focal lesion. Similar findings have been reported by other studies (1,21,27,30).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in nine different genes (ABCC8, KCNJ11, GLUD1, GCK, HADH, SLC16A1, subunits: Kir6.2 encoded by KCNJ11 and SUR1 encoded by ABCC8 gene (2). Both genes are localised in the 11p15.1 region and mutations in these accounts for the majority of CHI patients (3,4,5,6,7,8,9,10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation